Medicinal Plant Diversity at Cham Chu Nature Reserve Area, Tuyen Quang Province - Oanh, Pham Thi; Phuong, Ngo Duc; Xuyen, Do Thi; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4738, 2018)
A total of 443 medicinal plant species were recorded in Cham Chu Nature Reserve Area belonging to 325 genera and 120 families. Most of the medicinal plant species in Cham Chu Nature Reserve Area are Angiosperms with 425 species (95.94%) (360 Dicotyledonae, 65 Monocotyledonae), 6 species belong to the Gymnosperms (1.35%), 10 species are Polypodiophyta (2.26%), Psilotophyta and Lycopodiophyta are only one species (0.23%). The richest 3 families are Euphorbiaceae with 22 (4.97%) species, Rubiaceae with 17 (3.83%) species and Asteraceae ranks third, with 16 (3.61%) species, respectively. When the medicinal plant of the area are analysed by Raunkiaer’s life form system, the results are follows as: phanerophytes 311 (73.18%), chamaephytes 45 (10.59%), hemicryptophytes 10 (2.355%), cryptophytes 33 (7.76%), and therophytes 26 (6.12%) species, respectively. Keywords Medicinal plant, Cham Chu, Tuyên Quang References [1] Solbrig O.T., From Genes to Ecosystems: A Research Agenda for Biodiversity. IUBS - SCOPE - UNESCO, Harvard, Cambridge, Massachusetts, 1991, p.124. [2] Mishra B.P., R.S. Tripathi, O.P. Tripathi and H.N. Pandey, Effect of disturbance on the regeneration of four dominant and economically important woody species in a broad-leaved subtropical humid forest of Meghalaya, northeast India, Cur Sci, 84 (2003) 1449. [3] Ramakrishnan P.S., K.G. Saxena and U.M. Chandrashekara, Conserving the Sacred for Biodiversity Management. Oxford and IBH Publication Co. Pvt. Ltd., New Delhi, India, 1998. [4] Phạm Hoàng Hộ, Cây cỏ Việt Nam, Tập 1-3. Nxb Trẻ Tp. Hồ Chí Minh, 1999-2000. [5] Trung tâm Nghiên cứu Tài nguyên và Môi trường, ĐHQGHN; Tổ chức Phát triển Hà Lan; Viện Sinh thái và Tài nguyên Sinh vật, Danh lục các loài thực vật Việt Nam, Tập 1-3, Nxb Nông nghiệp, Hà Nội, Việt Nam, 2001-2005. [6] Lecomte H. (Edit.), Flore generale de l Indo-chine, 7 tomes, Paris, France, 1907-1951. [7] Vo Van Chi, Dictionary of medicinal plant of Vietnam, Med. Publ. House, Ho Chi Minh city, 1998. [8] Mabberley D.J., The Plant Book, Cambridge University Press, UK, 1987. [9] Nguyễn Nghĩa Thìn, Cẩm nang nghiên cứu đa dạng sinh học, Nxb Nông nghiệp, Hà Nội, Việt Nam, 1997. [10] Do Tat Loi, Medicinal plants and drugs of Vietnam, Med. Publ. House, Hanoi, 2001. [11] Batalha M.A., F.R. Martins, Floristic, frequency and vegetation life-form spectra of a Cerrado Site, Braz J Biol, 64 (2004) 203. [12] Raunkiaer C., The Life Forms of Plants and Statistical Plant, Geography, Oxford: Clarendon Press. (1934). [13] http://www.iucnredlist.org/search [14] Bộ Khoa học và Công nghệ, Viện khoa học và Công nghệ Việt Nam, Sách Đỏ Việt Nam (phần II - Thực vật), Nxb Khoa học Tự nhiên và Công nghệ, Hà Nội, 2007.